IMPLEMENTASI UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM MENANGANI PENYEBARAN BERITA BOHONG (HOAX) DI KOTA SAMARINDA - Wahyuni Safitri; Yolanda Mustika Wati (Law Department, University of Widya Gama Mahakam Samarinda, 2022)
Fake news (hoax) is information that is actually not true. In its distribution, it is necessary to handle and make efforts so that fake news (hoax) is not spread to the public as public consumption. In this research, researchers utilized the type of Normative Juridical Research. Another term for normative research is doctrinal research, also called library or document research. Type The Department of Communication and Information (Diskominfo) of Samarinda City needs to tighten the handling and efforts, the article is that fake news (hoax) is often spread widely so that people believe in the fake news (hoax). Law Number 19 of 2016 concerning Electronic Information and Transactions regulates the spread of hoaxes in article 28 paragraph (1), so that an action is needed by the Samarinda City Communication and Information Office (Diskominfo) and seeks to spread false news (hoax). is not disseminated to the public.